2006
DOI: 10.1177/000331970605700203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propionylcarnitine on Changes in Endothelial Function and Plasma Levels of Adhesion Molecules Induced by Acute Exercise in Patients with Intermittent Claudication

Abstract: In patients with intermittent claudication, treadmill exercise may cause acute deterioration of endothelial function and increase in plasma concentrations of adhesion molecules. The authors evaluated the efficacy of intravenously administered propionylcarnitine (PLC)in preventing these phenomena. Thirty-six claudicants with postexercise decrease in brachial artery flow-mediated dilation (FMD)were randomized to either placebo or PLC (600 mg as a single bolus followed by 1 mg/kg/min for 60 minutes).In the 18 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…Prior studies have shown that flow-mediated dilation (FMD) of the brachial artery is markedly reduced following maximal exercise in these patients (56,57). Intravenous infusion of vitamin C prevents the reduction in FMD, which indicates that this abnormal response is mediated, at least in part, by oxidative stress (57).…”
Section: Effects Of Nac On Vascular Function and Exercise-induced Infmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that flow-mediated dilation (FMD) of the brachial artery is markedly reduced following maximal exercise in these patients (56,57). Intravenous infusion of vitamin C prevents the reduction in FMD, which indicates that this abnormal response is mediated, at least in part, by oxidative stress (57).…”
Section: Effects Of Nac On Vascular Function and Exercise-induced Infmentioning
confidence: 99%
“…Another possibility is that, if present, the impairment in leg vascular function following exercise is very brief. In the studies of Silvestro and coworkers (56,57), the postexercise assessment of FMD was performed shortly after the maximal exercise bout, while our measurements of postocclusive hyperemia were conducted 30 min following the completion of the exercise bout. Additional studies are warranted to determine the time course of changes in vascular function in response to exercise in these patients.…”
Section: Effects Of Nac On Vascular Function and Exercise-induced Infmentioning
confidence: 99%
“…It was derived from previous observations that FMD additionally decreased in PAD patients shortly after exercise-induced maximal tolerable leg ischaemia. 5,6 To assess the duration of this phenomenon, we extended the observation time to 4 hours. Therefore, we followed the time course of changes in FMD of the clinically unaffected brachial artery after acute exercise-induced leg ischaemia in PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 15 patients with IC, exercise-induced increases in serum levels of E-selectin, P-selectin, L-selectin, and other chemokines were significantly reduced with the administration of oral propionyl L-carnitine 2 g/day for 2 months [51]. In a more recent study [52], a single intravenous (i.v.) dose of propionyl L-carnitine 600 mg in 18 claudicants significantly attenuated the exercise-induced decrease in FMD, whereas administration of placebo had no effect on this parameter.…”
Section: Pharmacodynamicsmentioning
confidence: 96%
“…Propionyl L-carnitine provides protection from the effects of oxidative stress and inflammation in ischemic tissue endothelium by reducing the plasma release of leukocyteendothelial adhesion cells [51,52], improving arteriolar function [53], and increasing arterial flow-mediated dilation (FMD) [52]. In 15 patients with IC, exercise-induced increases in serum levels of E-selectin, P-selectin, L-selectin, and other chemokines were significantly reduced with the administration of oral propionyl L-carnitine 2 g/day for 2 months [51].…”
Section: Pharmacodynamicsmentioning
confidence: 99%